Household Enterprises in Sub-Saharan Africa : Why They Matter for Growth, Jobs, and Livelihoods - Fox, Louise; Sohnesen, Thomas Pave (World Bank, Washington, DC, 2013)
Despite 40 percent of households relying on household enterprises (non-farm enterprises operated by a single individual or with the help of family members) as an income source, household enterprises are usually ignored in low-income Sub-Saharan-African development strategies. Yet analysis of eight countries shows that although the fast growing economies generated new private non-farm wage jobs at high rates, household enterprises generated most new jobs outside agriculture. Owing to the small size of the non-farm wage job sector, this trend is expected to continue for the foreseeable future. This analysis of enterprises and their owners shows that although it is a heterogeneous sector within countries, there are many similarities across countries, indicating that cross-country learning is possible. For labor force participants who want to use their skills and energy to create a non-farm income source for themselves and their families, household enterprises offer a good opportunity even if they remain small. The paper finds that given household human capital and location, household enterprise earnings have the same marginal effect on consumption as private wage and salary employment. The authors argue that household enterprises should be seen as part of an integrated job and development strategy.